«Golden Crowd» – Engaging the Users That Deliver on Your Crowdsourcing Goals - Volker Bilgram; Alexander Hahn; Johann Füller (Marketing Review St.Gallen, 2022)
Companies run branded crowdsourcing contests to achieve two main goals: generate ideas and create brand equity. This paper provides an empirical typology of contest users and reveals five distinct user types: jacks-of-all-trades, devoted brand fans, pure innovators, reward seekers and passive customers. Based on the users' characteristics we derive actionable insights on how to attract, recruit and manage the crowd for different purposes.
Keywords: 650